Pengaruh Intellectual Capital Pada Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening - Fitriasari, Ni Made Ayu Dwi; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p02, 2019)
This study aims to determine the effect of intellectual capital on firm value and financial performance as an intervening variable. This research was conducted on banking companies listed on the Indonesia Stock Exchange in 2014-2016, namely as many as 43 companies. Samples were taken using non-probability sampling techniques with purposive sampling method, so that 33 companies were selected with 99 total observations. Data analysis techniques use path analysis techniques. The results of the analysis prove that companies that are able to process intellectual capital well will affect financial performance, companies that are able to process intellectual capital well will affect the value of the company, companies that are able to process financial performance well will affect company value, and financial performance is able to mediate the relationship between intellectual capital in the value of the company. Keywords :Intellectual capital, company value, financial performance